MUTU BRIKET ARANG KULIT BUAH KAKAO DENGAN MENGGUNAKAN KANJI SEBAGAI PEREKAT - M. Natsir Usman (Forestry Faculty of Universitas Hasanuddin, 2007)
The development of an alternative energy is now becoming important due to the decrease of natural energy source, The current research was conducted to observe the quality of making charcoal briquette from cocoa pod shell with the particle size of 30 mesh, 50 mesh, 70 mesh and 7 % starch as adhesive. The result showed that charcoal particle size of 70 mesh gave the best charcoal briquette quality having characteristics: moisture 10.67 %, density of 1.15 g/cm3, 18.98% ash content, 49.93 % fixed carbon, 24.99% volatile matter and the calorific value of 4372.54 cal/g. Charcoal briquette from cocoa pod shell was utilized as alternative energy. Key words: Cocoa pod shell, charcoal briquette, starch as adhesive. References